Mouse Models of Hereditary Haemorrhagic Telangiectasia: Recent Advances and Future Challenges - Tual-Chalot, Simon; Oh, Paul; Arthur, Helen M. (Frontiers in Genetics, 2015)
Hereditary Haemorrhagic Telangiectasia (HHT) is a genetic disorder characterised by a multi-systemic vascular dysplasia and haemorrhage. The precise factors leading to these vascular malformations are not yet understood and robust animal models of HHT are essential to gain a detailed understanding of the molecular and cellular events that lead to clinical symptoms, as well as to test new therapeutic modalities. Most cases of HHT are caused by mutations in either endoglin (ENG) or activin receptor like kinase 1 (ACVRL1, also known as ALK1). Both genes are associated with TGFβ/BMP signalling, and loss of function mutations in the co-receptor ENG are causal in HHT1, whilst HHT2 is associated with mutations in the signalling receptor ACVRL1. Significant advances in mouse genetics have provided powerful ways to study the function of Eng and Acvrl1 in vivo, and to generate mouse models of HHT disease. Mice that are null for either Acvrl1 or Eng genes show embryonic lethality due to major defects in angiogenesis. However mice that are heterozygous for mutations in either of these genes develop to adulthood with no effect on survival. Although these heterozygous mice exhibit selected vascular phenotypes relevant to the clinical pathology of HHT, the phenotypes are variable and generally quite mild. An alternative approach using conditional knockout mice allows us to study the effects of specific inactivation of either Eng or Acvrl1 at different times in development and in different cell types. These conditional knockout mice provide robust and reproducible models of arteriovenous malformations, and they are currently being used to unravel the causal factors in HHT pathologies. In this review, we will summarize the strengths and limitations of current mouse models of HHT, discuss how knowledge obtained from these studies has already informed clinical care and explore the potential of these models for developing improved treatments for HHT patients in the future.